O Sistema de Gestão do Ressarcimento ao SUS: análise de seu desempenho no período 2011-2014 - Fernandes, Rogerio Baptista Teixeira (2015)
The reimbursement to the Unified Health System (SUS), created by Law No. 9.656 of 1998, showed impressive results in the period 2011-2014, compared to the period 2007-2011. This exploratory study analyzes the reimbursement to the SUS, its origin, legal support, juridical basis, organization, functioning, operating performance and effectiveness, focusing on results achieved in the period 2011-2014. In order to accomplish, the author relied on previous studies, official documents and reports, legislation, judgments of the Court of Audit and lawsuits filed before the Supreme Court. The analysis indicates that the results achieved in the last four years are promising, reflecting a favorable scenario for the consolidation of reimbursement to SUS as an important regulatory instrument for the supplementary health sector.